Pain, dietary habits and physical activity of children with developmental disabilities in Croatia, North Macedonia and Serbia: a cross-sectional study - Međaković, Jelena; Čivljak, Antonia; Zorchec, Tatjana; Vučić, Vesna; Ristić-Medić, Danijela; Veselinović, Aleksandra; Čivljak, Marta; Puljak, Livia (Springer Science and Business Media LLC, 2024)
Multiple studies have shown that children with developmental disabilities (CDD) often live with unrecognized and untreated pain, consume inadequate diet and have inadequate levels of physical activity. This study aimed to analyze pain, dietary habits and physical activity of CDD in Croatia, North Macedonia and Serbia. Methods A cross-sectional study was conducted in Croatia, North Macedonia and Serbia in March–April 2023 within the Erasmus+ SynergyEd project. The study included parents and caregivers of CDD. Data were collected via online survey. Results We included 954 participants from Croatia (N=543; 57%), North Macedonia (N=205; 21%) and Serbia (N=206; 22%). Participants reported that 16% of children suffered from chronic pain related to their condition. The main findings of our study are that chronic pain is prevalent in CDD (16%). Almost half (48%) of participants avoid certain foods for their children. The majority of children (86%) were not on a special diet. Among those that were on a special diet, they were most commonly (60%) on a gluten-free diet. Most (54%) participants stated that their children used nutritional supplements. Less than half participants (45%) stated that the child is involved in some kind of physical activity. Only 17% of CDD engaged in physical activities 5 h or more per week. Conclusion Our findings indicate that chronic pain, inadequate dietary patterns and insufficient physical activity are common in CDD from Croatia, Macedonia and Serbia. Education of parents and caregivers can mitigate their use of interventions that have not been proven effective, such as for example the use of gluten-free diets in CDD.
Keywords: Children with developmental disabilities; Pain; Nutrition; Physical activity